Leading Changes to Professional Training in the Multigenerational Office: Generational Attitudes and Preferences toward Learning and Technology. Issue 2 (8th January 2019) - Lowell, Victoria L.; Morris, James
Abstract : A multigenerational workforce is now commonplace, and research has shown that historical context and generational experiences affect the values, attitudes, and working and learning preferences of each generation. Therefore, organizations' awareness of the demographic profile of their internal talent and external talent from which they may recruit is needed to ensure they are cognizant of their employees' needs. Training leaders can serve as a valuable resource for businesses and their employees by offering support in learning and technology. To assist with the needs of this changing employee workforce, training leaders will need to consider generational attitudes and preferences regarding learning and technology to develop effective training that serves both the business and the employee. In this narrative review, the authors discuss generational attitudes towards learning and technology to assist training leaders in understanding the needs of the current multigenerational workforce and to provide actionable guidance for training multigenerational learners.